Analisis Faktor-Faktor yang Mempengaruhi Prestasi Belajar Taruna Manajemen Transportasi Udara Angkatan II di Politeknik Penerbangan Surabaya - R. Moh. Radix Agustiono; Aulia Regia S.P (Jurnal Penelitian)
Achievement of learning achieved by cadets is essentially a reflection of the learning effort. In general the better the learning effort the better the achievements achieved. Of course this is not independent of factors that influence it, among others, interest, motivation, education level of parents, income levels of parents, and so forth. This study discusses the influence factors of interest, motivation, level of old age education, income level of parents, and the number of children dependent parents on learning achievement cadet at Aviation Polytechnic of Surabaya Analysis techniques used descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis obtained data that cadets air transportation managementat Aviation Polytechnic of Surabaya has (1) interest in learning of 76.53% included in the high category; (3) parent education level 43,88% high school education, including in medium category; (4) income level of old roang 50% having income more than Rp 1,000,000, - per month, included in high category; and (5) parents of students who have dependents of 3-4 children as much as 44.90%, included in the medium category. The learning achievement of airport electrical cadet at Aviation Polytechnic of Surabaya is classified in very satisfactory category, that is 67.35% of students have Achievement Index between 2.76 to 3.50. The result of inferential statistic analysis concludes that interest (X1), learning motivation (X2), parent's education level (X3), parent's income level (X4), and number of parent dependent children (X5) together influence learning achievement (Y) the airport electrical engineering cadet at Aviation Polytechnic of Surabaya shown by the value of Fhitung of 11.275 is greater than the Ftable value of 2.30. The pattern of influence between these six variables is expressed by multiple regression equations: Y = 1,233 + 0,011 X1 + 0,014 X2 + 0,004 X3 + 0,005 X4 + 0,002 X5.